2021
DOI: 10.1108/prt-07-2021-0085
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus sabdariffa L. calyces’ and argon DBD plasma: potential eco-friendly cleaners for fire-damaged silver gelatin prints

Abstract: Purpose This paper aims at examining the potentiality of using Hibiscus sabdariffa L. calyces’ (Hs) aqueous extract to remove soot stains from the surface of fire-damaged silver gelatin prints. It further studies the cleaning efficiency and impact of both a contact method and a noncontact method with argon dielectric barrier discharge plasma (DBD Ar. plasma) on the different properties of silver gelatin prints. Accordingly, it prompts using economic, eco-friendly materials and methods in the photograph conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Despite the close interconnection between paper and photography conservation, the use of gels in this last field remains limited to date. Some research on cleaning photographic prints has been done, but more systematic research on silver gelatine prints is still needed [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the close interconnection between paper and photography conservation, the use of gels in this last field remains limited to date. Some research on cleaning photographic prints has been done, but more systematic research on silver gelatine prints is still needed [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This did not cause any major physical or chemical changes on the surface that had been treated with plasma. Alatter, et al, [32] demonstrated that DBD Ar. plasma, a non-contact approach, when mixed with the aqueous extract, cleaned the surface of historical images without leaving stains or causing damage.…”
Section: Introductionmentioning
confidence: 99%